Implementation and Evaluation of a Novel Media Education Curriculum for Pediatric Residents - Rashi Kabra; Shara Steiner; Jane Cerise; Nadia Saldanha (MedEdPORTAL, 2023)
Introduction Despite increasing awareness of media exposure to children and adolescents and the known value of media education for physicians, residency programs lack formal media education. Methods We designed an interactive curriculum for pediatric residents to teach health effects of media as well as screening and counseling strategies. Instructional methods were based on constructivism, experiential learning, and situated learning theories. Participants independently reflected on a media viewing, then participated in two facilitator-led 1-hour workshops of two to three residents. Facilitators received speaker notes based on American Academy of Pediatrics media guidelines. Changes in knowledge, reported skills, and attitudes were assessed by pre- and posttests. Results Twenty-one residents completed the curriculum from September 2021 through April 2022. Knowledge improved after the curriculum as the median score increased from 3 to 5 out of 6, although 4 months later it was insignificant. Reported skills in screening did not significantly change. Residents strongly agreed that media use was an important health issue, with medians of 9 or 10 out of 10 on all tests. Attitudes regarding residency preparedness and confidence in screening and counseling significantly improved from pretest medians of 6 and 6 out of 10, respectively, to posttest medians of 8 and 9 to 4-month posttest medians of 6 and 8. Discussion A media curriculum for pediatric residents resulted in improved knowledge and attitudes. Enhanced attitudes demonstrated sustainability. All participants found the curriculum relevant and engaging and felt it should be continued.